An RF Stress-Based Thermal Shock Test Method for a CMOS Power Amplifier - Shaohua Zhou (IEEE, 2021)
To accelerate the degradation of critical specifications of CMOS power amplifiers (PAs), this paper proposes a new measurement method that introduces radio frequency (RF) stress in the thermal shock test of CMOS PAs. The experimental results show that the proposed method is effective. The degradation of key PA specifications such as output power and power-added efficiency can accelerate under RF stress. Its degradation speed is faster than that under no RF stress. Possible reasons for the degradation of crucial PA specifications accelerated by RF stress are discussed and analyzed in detail in this paper. The method proposed in this paper can effectively reduce the measurement time and cost to study the degradation of critical specifications of the CMOS-based PA. This method can be used for scientific research on the performance degradation of microwave/RF circuits and devices and aging experiments of electronic products before they leave the factory.